2020
DOI: 10.29103/ijevs.v2i11.3004
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Kahoot in Improving Students’ Tenses Understanding in Higher Education

Abstract: Tense is a part of English grammar that becomes something difficult to understand by students. Therefore, it needs interesting and creative learning media to face that problem. This research purposes to evaluate and analyze the implementation of Kahoot as a digital learning media in improving students’ understanding about tenses in higher education. There were 15 students in Civic Department of Education Faculty in Universitas Tompotika Luwuk as the sample of this research. Mix method in concurrent embedded st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…This finding shows that most students had positive response toward this item. Moreover, this finding is similar to the research finding by Nurlalela and Nawir (2020) who argues that Kahoot can help students in improving students knowledge about the use of English tenses; learning tenses which is judged as a boring activity with traditional method becomes an interesting activity after the use of Kahoot in learning English tenses. Hence, if the students always being involved in Kahoot games about English, there is a bigger possibility for them to better at English as what they believe.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…This finding shows that most students had positive response toward this item. Moreover, this finding is similar to the research finding by Nurlalela and Nawir (2020) who argues that Kahoot can help students in improving students knowledge about the use of English tenses; learning tenses which is judged as a boring activity with traditional method becomes an interesting activity after the use of Kahoot in learning English tenses. Hence, if the students always being involved in Kahoot games about English, there is a bigger possibility for them to better at English as what they believe.…”
supporting
confidence: 88%
“…The other sign is students put more attention in the classroom; they are not easily to be distracted (Perdana, Saragi, & Aribowo, 2020). In addition, students also show their excitement for every activity conducted in the classroom (Nurlalela & Nawir, 2020). Thus, it is obvious the students' responses in this research shows that they are motivated because of the use of Kahoot.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In the history of the error analysis in using Tense on the various articles in Indonesia, the articles on the field of Education have always been more updated than the articles on the field of Linguistics, especially during the pandemic and the post-pandemic of Covid-19 (e.g., (Iqbal & Arfan, 2020); (Badroeni & Zakaria, 2020); (Nurlaela & Nawir, 2020); (Kartika, Nengseh, Kinanati, & safitri, 2020); (Tahang, 2020); and (Napitupulu, 2021)). Even though there are a lot of tense analysis studies in linguistics, most of them have only demonstrated the error use of the tense type in omission, misinformation, and miss-ordering of the structure of the simple tense aspects in the written data of student proficiency tests (e.g., (Fitria, 2020); (Juliana, Purbarini, & Iskandar, 2020); (Setiani & Saragih, 2020); (Vera, 2020); (Perlin, Sartika, & Nery, 2021); (Sari, 2021); (Rohana & Harahap, 2022); (Syukur & Supraba, 2022); (Fadilah, 2022); and (Fitri & Suryani, 2022)).…”
Section: Introductionmentioning
confidence: 99%